2005
DOI: 10.1111/j.1529-8019.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Itch, pain, and metaesthetic sensation

Abstract: Itch is one of the alarm sensations that human beings have phylogenetically evolved for a defense purpose. Many theories and evidences regarding the biological, pathophysiological, and clinical aspects have been given, but an update on the neuroanatomy paths and consequent treatments is required. Some chemicals that are released after skin injury and facilitate the inflammatory process can induce itch or pain or basically lead to a sensitization of the nociceptor response. In clinical practice, the present aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Since this difference in perception is most probably because of a central processing, this may be proposed as one potential portal of psychological factors to contribute in the pathogenesis of LSC. [22][23][24] Chronic pruritus of unknown etiology has been considered as a 'somatoform' disorder in some clinical situations. 25 In this p o l i s h a n n a l s o f m e d i c i n e x x x ( 2 0 1 6 ) x x x -x x x regard, concordance of other somatic symptoms, as was noted in LSC patients in the current study, is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Since this difference in perception is most probably because of a central processing, this may be proposed as one potential portal of psychological factors to contribute in the pathogenesis of LSC. [22][23][24] Chronic pruritus of unknown etiology has been considered as a 'somatoform' disorder in some clinical situations. 25 In this p o l i s h a n n a l s o f m e d i c i n e x x x ( 2 0 1 6 ) x x x -x x x regard, concordance of other somatic symptoms, as was noted in LSC patients in the current study, is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that we could increase the secretion of SP in cells exposed to trypsin. Similarly, incubation of the cocultured cells with papain, a cysteine protease known for its ability to induce neurogenic inflammation in a manner independent of PAR2 activation (45)(46)(47)(48)(49), also increased SP secretion in vitro. Collectively, these results indicate that our model adequately mimics the in vivo activation and modification of SP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Key words: pruritus; atopic dermatitis; somatosensory evoked potentials; long-latency evoked potentials to thermal stimulation; CHEPS; thin sensory fibres. Pruritus or itch is defined as a cutaneous sensation that provokes a desire to scratch (1,2). Pruritus is one of the most common symptoms of skin diseases, and is thus of increasing interest.…”
mentioning
confidence: 99%